Moral terror from shame crimes: The perspective of the political and religious divide between two generations in Iraq - Jassim, Sarmad Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
Moral panic is one of the modern concepts and includes religious, social, political and cultural dimensions, and it also serves as an individual and social reaction to behaviors, attitudes and issues of a condemned nature at the level of religion and law and with political roots , including crimes of "washing shame ,"so the current research aimed to know the concept panic the moral part of" honor" crimes , and identifying the features of the political divide - cultural between the generation thousandth of a Li- generation Alalveni, as part of heme NH political and legal chaos in our society, and comparing the features of the gap of cultural from the perspective of the generation of the twentieth century and generation Alalveni with Related to moral panic in the context of "shame" crimes. The research included three chapters, adopted the method of analysis, discussion and review of previous studies and scientific literature regarding the variables of the current research, and an attempt to reach approaches and paradoxes to it with the Iraqi reality, through the first chapter " :moral panic in the context of crimes of" washing shame , " and the second chapter " gap cultural between the twentieth century generation and generation Alalveni ," as the researcher discussed this gap and its causes and ways in which is the responsibility of specialists in the treatment of deviant behavior followed in this crime , and the statement of the position of the Sharia of the Islamic of this crime and how to deal with her and judgment legitimate on the perpetrators of her and automated data used to prove her , as a person ’s political engines to the bullying of the perpetrators of these crimes. The researcher concluded some indications about the research variables that he used as theoretical premises for research procedures in his third chapter, which included preparing a questionnaire to measure the moral panic from crimes of shame washing from the perspective of the cultural-political and religious gap between the pre-2003 generation and beyond, and extracting the standard characteristics of the questionnaire from honesty and consistency. The researcher applied the research tool to (140) individuals, at the rate of (40) people born in 1981 and (100) people born in the year (2000). The results showed that there is a high level of cultural panic over the crimes of washing shame of the millennial generation unlike the first millennium generation, And that there is a cultural, political and religious gap between the two generations regarding this crime, and that there is a wrong and distorted understanding of the Islamic religion regarding this crime. The research includes a set of recommendations , including amending laws dealing with honor crimes related to them , and the involvement of young people, especially from generation Alalveni political issues , and bridge the gap between the generation yen by devoting the benefits of nuclear family , and educate young people in the social networking sites not to post The horrific pictures and videos of crimes of shame washing to reduce moral panic in society , and sensitize tribal and tribal societies, parties and political entities of the necessity of not embracing religion to justify crimes and behaviors that heighten moral panic in society and increase the cultural and political gap between them and the millennial generation.